Recent advances and existing challenges in the design of bridge falsework systems - André, J. (2013)
Bridge falsework systems are frequently used in the construction, rehabilitation and retrofit works of bridge structures. These structures have a significant impact on the cost, construction rate and construction safety of the supported permanent structures. However, the relevant stakeholders often do not consider them as important as permanent structures, and in recent years, a high number of accidents involving bridge falsework systems have been reported.A research programme was initiated aiming to contribute to a better knowledge about the structural behaviour, reliability and robustness of bridge falsework systems. In this paper, the advances and existing challenges in the design of bridge falsework systems will be summarised. Additionally, the basis of a framework for the structural design of these structures within the context of a risk-informed decision-making is presented.